Chronic, Elevated Maternal Corticosterone During Pregnancy in the Mouse Increases Allergic Airway Inflammation in Offspring - Smith, Arianna L.; Paul, Emmanuel; McGee, Devin; Sinniah, Ranuka; Flom, Emily; Jackson-Humbles, Devan; Harkema, Jack; Racicot, Karen E. (Frontiers in Immunology, 2020)
Allergic asthma is a chronic pulmonary disorder fundamentally linked to immune dysfunction. Since the immune system begins developing in utero, prenatal exposures can affect immune programming and increase risk for diseases such as allergic asthma. Chronic psychosocial stress during pregnancy is one such risk factor, having been associated with increased risk for atopic diseases including allergic asthma in children. To begin to define the underlying causes of the association between maternal stress and allergic airway inflammation in offspring, we developed a mouse model of chronic heightened stress hormone during pregnancy. Continuous oral administration of corticosterone (CORT) to pregnant mice throughout the second half of pregnancy resulted in an ~2-fold increase in circulating hormone in dams with no concomitant increase in fetal circulation, similar to the human condition. To determine how prolonged heightened stress hormone affected allergic immunity in offspring, we induced allergic asthma with house dust mite (HDM) and examined the airway immune response to allergen. Female mice responded to HDM more frequently and had a more robust immune cell response compared to their male counterparts, irrespective of maternal treatment. Male offspring from CORT-treated dams had a greater number of inflammatory cells in the lung in response to HDM compared to males from control dams, while maternal treatment did not affect immune cell numbers in females. Alternatively, maternal CORT caused enhanced goblet cell hyperplasia in female offspring following HDM, an effect that was not observed in male offspring. In summary, prenatal exposure to mild, prolonged heightened stress hormone had sexually dimorphic effects on allergic inflammation in airways of adult offspring.